IMPLEMENTASI STANDAR NASIONAL PERPUSTAKAAN (SNP) PERKA NOMOR 13 TAHUN 2017 OLEH PERPUSTAKAAN UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG - Bagas Aldi Pratama (Publication Library and Information Science, 2023)
The application of the National Library Standard for university libraries must be prioritized to support quality and quantity. Starting from complaints from students of the new study program regarding reference needs that have not been met their information needs. This study uses a descriptive qualitative approach with the aim of knowing the availability of references for FTIK and FUAD students in the UIN SATU Tulungagung Library. Data collection through observation, interviews, and documentation. The results of the study show that the availability of references for users from various study programs has not been evenly distributed. Most of the old study programs in FTIK and FUAD have been fulfilled. Meanwhile, the new study program must be considered regarding its reference needs. The pressure point that is the top priority in the compulsory books of each study program. In addition, local content-based collections have not been processed optimally so that the existence cannot be utilized optimally. The existence of inhibiting factors such as lack of budget, campus policies, not optimal collection development, and integrated services with faculty libraries have not been implemented. In the future, these factors must be above so that the needs of users regarding the availability of collections can be met